Очистка растворов от дисперсных примесей методом электрокоагуляции. Осаждение глинистых примесей при переменных гидродинамических режимах, факторный эксперимент - Донченко, М. И.; Срибная, О. Г.; Гончаров, Ф. И.; Штепа, В. Н. (НТУ "ХПИ", 2009)
За допомогою факторного експерименту досліджено процес очистки модельного розчину, який імітує річкову воду, від глинистих завислих речовин. Лабораторні випробування методу електрокоагуляції на реальному об’єкті – стічних водах птахофабрики – показали, що після 30-40 хвилин відстоювання обробленої води концентрація дисперсних домішок знижується майже в 100, а органічних речовин – приблизно в 10 разів.

The process of the purification of the model solution, which imitates the river water, from the clay admixtures has been investigated with the using of the factorial experiment. The laboratory tests of the electrocoagulation method on the real object (sewage of poultry factory) showed that after 30-40 min. of the settling of pretreated water the concentration of dispersed impurity was reducedalmost in 100 times, and organic substances-approximately in 10 times.
Keywords: сточные воды; птицефабрики; органические соединения; стальные аноды; гидроксиды железа; хлорид-ионы